The role of Growth Differentiation Factor 15 in Acquired Muscle weakness in ICU - Aya Hamdy Ahmed; Amany Khairy Abuelhussein; Omyma Shehata Mohamed; Zaki Mohamed Zaki (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: ICU-acquired weakness (ICU-AW) is a significant problem in very sick patients. It can cause more time on breathing machines, longer hospital stays, and a greater chance of dying. Even though it’s important to diagnose it early, it’s hard since the typical ways of assessment are limited. Objective: The current study discusses the use of Growth Differentiation Factor 15 (GDF-15) as a diagnostic and predictive marker of ICU-AW and shows its correlation with muscle wasting and patient outcomes. Methods: An analysis was conducted to explore the correlation of plasma GDF 15 level with the incidence of ICUAW and its utility as an early diagnostic biomarker, as well as any change in the urea-creatinine ratio in ICU-AW and any correlation with the GDF 15 level. Results: High levels of GDF-15 were strongly associated with muscle wasting, metabolic stress, and adverse outcomes in ICU patients. As compared to conventional diagnostic methods, GDF-15 has better potential to identify and predict ICU-AW in an early phase. Conclusion:GDF-15 holds great promise as a biomarker for ICU-AW, offering valuable help in early diagnosis and treatment. Its clinical applications and the modes of treatments associated with GDF-15 need further studies to bring down muscle losses in critically ill patients.